Distressed Hedge Funds in Secondary Sovereign Debt Markets of Emerging Economies - Oluyeju, Olufemi; Oluyeju, Maria (Acta Universitatis Danubius. Juridica, 2024)
The paper aims to interrogate the effects of distressed hedge funds (DHFs) investments on the liquidity in the secondary market for sovereign debt of emerging economies. DHFs, or vulture holdouts, as they are informally known, have gained significant prominence in recent national debt crises. The primary complaint against them is that they exploit cooperative creditors and sovereign debtors by purchasing distressed debt at reduced prices, choosing not to participate in debt restructuring processes, and pursuing litigation to recoup the total debt amount. However, writers and industry experts have argued that although the activities of the holdout creditors, especially the DHFs, could disrupt the orderly sovereign debt restructuring in the debt market, much more beyond that, they promote the deepening and liquidity of the market. Thus, in pursuit of profits, distressed asset investors unintentionally contribute to the market’s good by fostering market liquidity and indirectly helping the bondholders, sovereign borrowers defaulted sovereigns, and the societies of the debtor nations and the nations where the sovereign debt market is situated. This study is essentially non-empirical; hence, the literature review is used as the methodological tool. Specifically, an integrative review is used because the literature serves as the data.